How Costly Is Affirmative Action? Government Contracting and California's Proposition 209 - Marion, Justin (The Review of Economics and Statistics, 2009)
This paper investigates the effect of disadvantaged business enterprise subcontractor goals on the winning bids for highway construction contracts using California's Proposition 209, which prohibited the consideration of race or gender in awarding state-funded contracts. After Proposition 209, prices on state-funded contracts fell by 5.6% relative to federally funded projects, for which preferences still applied. Most of the price decline after Proposition 209 resulted from the mix of subcontractors employed, which seems to arise from the higher costs of firms located in high-minority areas. Finally, short-run barriers to entry and expansion may increase the cost of affirmative action.